Surgery of atlantoaxial dislocation by Posterior Decompression Fusion & Fixation at Lateral Mass Screw of C1 & Pedicle Screw & Rod by C2: A Study of 30 Cases - Nath, Haradhan Deb; Barua, Kanak Kanti; Banyea, Purusttam; Biswas, Pulak Kumar; Halder, Rathin; Ahsan, Md Ashik (Bangladesh Journal of Neurosurgery, 2021)
Background: Atlantoaxial dislocation (AAD) is a potentially fatal disturbance to the normal occipital-cervical anatomy that affects some populations disproportionately, which may cause permanent neurologic deficits or sagittal deformity if not treated in a timely and appropriate manner. Methods: This was a cross sectional study, which was carried out at the Department of Neurosurgery, Bangabandhu Sheikh Mujib Medical University from July 2010 to June 2017. We have studied 30 patients of atlantoaxial subluxation. After collecting patient admission data a brief history and clinical examinations were done. We have conducted a retrospective analysis of the outcomes of 30 consecutive spinal surgeries performed for AAS patients, by posterior decompression, fusion & fixation at lateral mass screw of C1 & pedicle screw & rod by C2 in all cases. We have compared our findings with a previous study. We also examined the factors related to poor outcomes. Result: From a surgical method perspective, the patients underwent post decompression, fusion & fixation at lateral mass screw of C1 & pedicle screw & rod by C2. After surgery, closed follow up was done. The highest age group was 21-40 years 40%. Most of the sufferer were male 80%. The commonest cause was road traffic accident 26.66%. The commonest clinical finding was quadriparesis 14(46.67%). The majority of the patients 24(80%) improved after surgery. In our present study after surgery neurological improvement rate is 83.33%, the rate of SSI was indeed high 10.00%, total death rate was 3.33%, the hardware failure rate was 3.33% and the reoperation rate reached 6.66%. Conclusion: The results of this study showed that the C1/2 fixation technique exhibited effectiveness in terms of neurological recovery. Bang. J Neurosurgery 2021; 10(2): 148-153